2012
DOI: 10.1590/s1516-35982012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and reproductive performance of grazing beef heifers bred at 18 months of age

Abstract: -The experiment was carried out to evaluate the performance and body development of beef heifers reared from 15 to 18 months of age on Pearl millet (Pennisetum americanum), Alexandergrass pasture (Urochloa plantaginea) or native pasture invaded by Annoni-2 grass (Eragrostis plana Nees). The experimental design was completely randomized following a repeated measure arrangement, with three treatments and two replications. The grazing method was continuous with variable stocking rate in order to maintain the swar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
3
1
2
Order By: Relevance
“…The values of forage mass, sward height, and forage allowance in this study were lower than those observed by Costa et al (2011), Souza et al (2012) and Oliveira Neto et al (2013 using the same forage. However, the heifers in these studies gained from 0.483 to 0.766 kg BW daily, which is comparable with the 0.732 kg day -1 gained by heifers exclusively grazing in our study, showing that the scale of variation of values for daily weight gain is small in response to different canopy components and the same animal performance is achieved with different sward managements.…”
Section: Discussioncontrasting
confidence: 84%
“…The values of forage mass, sward height, and forage allowance in this study were lower than those observed by Costa et al (2011), Souza et al (2012) and Oliveira Neto et al (2013 using the same forage. However, the heifers in these studies gained from 0.483 to 0.766 kg BW daily, which is comparable with the 0.732 kg day -1 gained by heifers exclusively grazing in our study, showing that the scale of variation of values for daily weight gain is small in response to different canopy components and the same animal performance is achieved with different sward managements.…”
Section: Discussioncontrasting
confidence: 84%
“…O maior teor proteico da folha de capim-annoni pode ser atribuído a algumas características da planta invasora como porte vigoroso, alta produção de massa verde, adaptação a solos pobres e resistência ao frio (16) e o surgimento de folhas novas. Avaliações da pastagem nativa com dominância de capim-annoni mostraram baixos teores de proteína bruta e fibra em detergente neutro (5,6; 71,6% e 4,1; 69,9%) durante a estação quente, que foram verificados quando as disponibilidades de forragem foram superiores a 5 ton/ MS/ ha (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) . Por outro lado, Alfaya et al (18) , avaliando feno de capim-anonni, observaram diminuição dos teores proteicos médios aproximados (7,8 a 5,3%), durante a primavera e verão referentes a cinco épocas de corte (30 a 150 dias).…”
Section: Resultsunclassified
“…Quando somado o fluxo de crescimento de colmos ao fluxo de crescimento de lâminas foliares, a eficiência potencial de utilização apresentou valor positivo. Nessa espécie, a manutenção de uma MF de 3000 kg ha -1 MS, mesmo com a maior parte da sua composição (63%) constituída por colmos, proporciona ganhos de 0,616 kg bezerra dia -1 e ganho por área de 347,6 kg ha -1 PC (Souza et al, 2012). Pinto et al (2001), avaliando a dinâmica de acúmulo de matéria seca em pastagem de Tifton 85, determinaram que a contribuição relativa do crescimento proveniente das hastes é, em média, 67,2%.…”
Section: Resultsunclassified